2019
DOI: 10.3386/w26345
|View full text |Cite
|
Sign up to set email alerts
|

The Gender Gap in Self-Promotion

Abstract: In job applications, job interviews, performance reviews, and a wide range of other environments, individuals are explicitly asked or implicitly invited to assess their own performance.In a series of experiments, we find that women rate their performance less favorably than equally performing men. This gender gap in self-promotion is notably persistent. It stays just as strong when we eliminate gender differences in confidence about performance and when we eliminate strategic incentives to engage in self-promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(47 citation statements)
references
References 5 publications
1
46
0
Order By: Relevance
“…This limitation raises the question for women with children that energy must be spent on positioning themselves to fit into a model that they still consider “different.” Second, women are less likely to self-promote than men (Dobbins et al, 1990 ; Oakley, 2000 ; Singh et al, 2002 ). This gender gap in self-promotion is reflective of the gender gap in self-evaluations and, in addition, the gender gap in self-evaluations is specific to evaluations of own performance (Exley and Kessler, 2019 ). Women evaluate their performance less favorably than men, which then is likely to have a continuing impact on their careers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This limitation raises the question for women with children that energy must be spent on positioning themselves to fit into a model that they still consider “different.” Second, women are less likely to self-promote than men (Dobbins et al, 1990 ; Oakley, 2000 ; Singh et al, 2002 ). This gender gap in self-promotion is reflective of the gender gap in self-evaluations and, in addition, the gender gap in self-evaluations is specific to evaluations of own performance (Exley and Kessler, 2019 ). Women evaluate their performance less favorably than men, which then is likely to have a continuing impact on their careers.…”
Section: Resultsmentioning
confidence: 99%
“…how does the potential for gender-specific backlash influence self-evaluations and how employers view self-evaluations? (Exley and Kessler, 2019 ). Future research should also consider the gender-oriented role of personal branding in private life.…”
Section: Discussionmentioning
confidence: 99%
“…Departments should consider appropriate salary points that are less reliant on negotiation, given that women are less likely to do so (Babcock and Laschever 2003). Men also may affirmatively work to notice and nominate worthy junior women for awards because women are less likely to self-promote (Exley and Kessler 2019). As departments recruit women to their positions, they also must prioritize the support necessary to achieve tenure.…”
Section: Discussionmentioning
confidence: 99%
“…The phenomenon of a gender gap in self-evaluation and self-promotion has been well documented in social science research. Exley and Kessler (2019) found that, between equally high-performing men and women, women would self-evaluate more poorly despite evaluating others similarly regardless of gender. Such a gender gap has been observed in traditionally male-dominated professions.…”
Section: Gender Gap In Self-promotionmentioning
confidence: 93%